Primary Sellar Lymphoma: Radiologic and Pathologic Findings in Two Patients - Kaufmann, Timothy J.; Lopes, M. Beatriz S.; Laws, Edward R.; Lipper, Maurice H. (American Journal of Neuroradiology, 2002)
Summary: We describe the clinical, MR imaging, and pathologic findings in two cases of primary sellar lymphoma in immunocompetent individuals. Both patients had hypopituitarism, and one patient had a sixth cranial nerve palsy. MR images depicted sellar and suprasellar masses in both patients, and extension into the cavernous and sphenoid sinuses was also present in one patient. The pathologic diagnosis in both cases was large B cell lymphoma.